Congenital Heart Disease in a Tertiary Care NICU; Pattern, Risk Factors and Outcome - Dey, Sanjoy Kumer; Hossain, Md Arif; Yasmin, Faria; Jahan, Ismat; Hassan Shabuj, Mohammad Kamrul (Bangladesh Journal of Child Health, 2024)
Background: Identification of congenital heart disease (CHD) is increasing, may be due to advancement of diagnostic technology and availability of trained man power. Several studies have been conducted in Bangladesh to identify the prevalence and pattern of CHD but paucity of data regarding etiology and outcome. Objective: The aim of this study is to identify the frequency and risk factors of so that preventive measures can be taken. Methods: This retrospective case control study was conducted in the neonatal intensive care unit (NICU), BSMMU, Dhaka from January 2021 to June 2022. All admitted neonates in NICU with the diagnosis of CHD were considered as cases. Twice number of newborn having gestational age and birth weight matched neonates diagnosed other than CHD in NICU were considered as control. Data were extracted from the Medical records of patient files and computer electronic data records of “Newborn Birth Defect (NBBD) surveillance in Bangladesh.” The level of significance was set at 5% (P <0.05). Result: Total 914 patient were admitted during the study period among them 119 patient were CHD (frequency rate 13%). Mean birth weight and gestational age of CHD group were 2376±783.85g & 35.80±3.26 weeks respectively. About 85.7% had acyanotic CHD, among them most prevalent were atrial septal defect (42%) then patent ductus arteriosus (11.8%). Cyanotic CHD were 17 (14.3%). Maternal DM significantly increase the risk of developing CHD, Odd’s ratio 1.971 (CI: 1.182 - 3.285). Death were more in CHD group (34.5%) than control group (20.4%), p values = 0.005. Conclusion: Frequency (13%) of congenital heart disease was high. Maternal diabetes mellitus increases the risk of developing CHD of their baby. Death were more among babies with CHD. BANGLADESH J CHILD HEALTH 2022; VOL 46 (3) : 122-129